Axonal Degeneration of the Vagus Nerve in Parkinson's Disease—A High-Resolution Ultrasound Study - Pelz, Johann Otto; Belau, Elena; Fricke, Christopher; Classen, Joseph; Weise, David (Frontiers in Neurology, 2018)
Background: Recent histopathological studies revealed degeneration of the dorsal motor nucleus early in the course of Parkinson’s disease (PD). Degeneration of the vagus nerve (VN) axons following neurodegeneration of brainstem vagal nuclei should be detectable by high-resolution ultrasound (HRUS) as a thinning of the VNs. Methods: We measured both VNs cross-sectional area (VN-CSA) of 35 patients with PD and 35 age- and sex-matched healthy controls at the level of the thyroid gland using HRUS. Results: On both sides, the VN-CSA was significantly smaller in PD patients than in controls (right: 2.1±0.4 vs. 2.3±0.5 mm², left 1.5±0.4 vs. 1.8±0.4 mm²; both p < 0.05). There was no correlation between the right or left VN-CSA and age, the Hoehn & Yahr stage, disease duration, the motor part of the Unified Parkinson's Disease Rating Scale score, the Montreal Cognitive Assessment score, or the Non-motor Symptoms Questionnaire and Scale for Parkinson’s disease score including its gastrointestinal domain. Conclusions: These findings provide evidence that atrophy of the VNs in PD patients can be detected in-vivo by HRUS.